Whole exome sequencing detects novel variants in Saudi children diagnosed with eczema - Neda M. Bogari; Amr A. Amin; Husni H. Rayes; Ahmed Abdelmotelb; Faisal A. Al-Allaf; Anas Dannoun; Hiba S. Al-Amodi; Anas A. Sedayo; Hilal Almalk; Amna Moulana; Rania Balkhair; Fatma Jambi; et al. (Elsevier, 2020)
Background: Eczema is also known as atopic dermatitis is well-known for the skin disease globally. In Saudi Arabia, exome sequencing studies have not been documented. The purpose of this study was to scrutinize the disease causing mutations in children affected with eczema with exome sequencing in the Saudi population. Methods: We recruited randomly three sporadic cases of children diagnosed with eczema and simultaneously, three more cases were adopted for control samples. Exome sequencing was carried out by applying a pipeline that captures all the variants of concern related to the samples by using the Ion torrent. Results: In this study, we have documented 49 variants, among which 37 variants were confirmed through eczema children and remaining 30 variants through control children. However, from the analysis of the 6 samples, we have identified rs10192157 (1646C > T; Thr549Ile), rs2899642 (27C > G; Asn9Lys), chr1:152127950 (1625 G > A; Gly542Asp) and chr1:152128041 (1534C > G; Gly512Arg) variants which are rarely linked to the disease eczema. In the rs10192157, we have documented these mutations in all three eczema children and one in the control; the rs2899642 mutation appeared in only a couple of eczema children, whereas the mutation in the chr1:152127950 regions appeared in only one eczema patient. However, the chr1:152128041 mutations appeared in only one case of eczema and also in two control children. Conclusion: Our study revealed four mutations which had not previously been connected with eczema within the database. However, the rs10192157 and rs2899642 mutations were documented with asthma disease. The remaining mutations such as chr1:152127950 and chr1:152128041 have not been reported anywhere else. This study recommends screening these 4 mutations in eczema cases and their relevant controls to confirm the prevalence in the Saudi population. It is recommended that future studies examine the 4 mutations in detail. Keywords: Eczema, Exome-sequencing, Mutation, Variants